As concepções de alfabetização e letramento de duas alfabetizadoras que atuam em escolas do campo no município de Palmeira das Missões - RS: uma reconstrução dos percursos formativos através de relatos autobiográficos - Batalha, Denise Valduga (2011)
This investigation looks for an approach of the literacy conceptions of two literacy teachers that act at rural schools in Palmeira das Missões - RS, through the teachers' autobiographical reports, Lene da Silva Santos and Rosemeri Soares, which take into account the formative processes of both starting from written narratives that are used of the memory and of the relived memories, rebuilt and contemplated by the process of turning student and teacher. The methodology used is based in an approach designated as qualitative investigation, according to Bogdan; Biklen (1994), Antunes (2001; 2010) and Deslandes (1994), because the researcher's interaction with the subject of the research is constituted in a significant element in that investigation type. The collection instruments of information are autobiographical reports, which Nóvoa (1992) believes that promote a formation process and provide the understanding of as it is configured certain conceptions, through the considered teachers' professional histories the collaborators of the investigation, being constituted, like this, in a form of to respect and to hear the collaborators' voice, that most of the time, is silenced and unknown. Besides, the interview is used, because for Bogdan; Biklen (1994), this is a technique that, when properly applied, presents high reliability and it has great importance for making possible to measure attitudes, opinions, behaviors and circumstances of the subject's life. For that, the collaborators' school memories are rescued through the reconstruction of the lived formative courses and relived by both. Political and conceptual subjects relative are brought to the teachers' formation in national extent and in the context of the rural school from Palmeira das Missões - RS. They are identified some literacy concepts constituted starting from a historical rescue and some fundamental considerations are introduced in the teaching of the language written in the perspective of the literacy in what refers to the rural school. It is verified that the reflection on the own history of educational life, as space of construction of knowledge for the road of the research, in the perspective of Nóvoa (1995), is to provoke the concern with an effective performance through the development of a theoretical and intentionally committed pedagogic work of larger consistence with a pedagogic project of professionals' more critical, reflexive and inventive formation, mediators of the transformations that the society always demands us.